Love as enjoyment: hopelessness, play and affective worlds of desire - Awal, A (Society for Cultural Anthropology, 2025)
Some young middle-class women in Ghaziabad have little hope that love will lead to a desirable future. Therefore, they kindle desire in casual encounters that they describe as “enjoyment” and cultivate a sensibility of living in the moment. Enjoyment departs from love (pyaar) as depicted in mass media like Bollywood that leads to marriage. Instead, through enjoyment, college-going women move through fantasies of love leading to marriage under conditions of urbanisation, the rise of women’s education, and pervasive unemployment. In the process, they uncouple flirting and erotic play from its progression to love or marriage. In so doing, women ironically and unintentionally create an alternate form of love. This version of love is playful, creative, and fun. It allows women to access pleasure and enact a version of love that is not latched to marriage. By paying attention to these alternate forms of love, this paper shows how women work past the “cruel optimism” of love, reconstituting it as a site for self-affirmation, pleasure, and play.